Open Smart Energy Eco-System for the Future. Issue 2 (November 2020) - Haghgoo, Maliheh; Dognini, Alberto; Storek, Thomas; Plamanescu, Radu; Rahe, Ulrike; Gheorghe, Stefan; Albu, Mihaela; Monti, Antonello; Dirk, Muller
Abstract: Due to the increasing complexity of the global energy system and the amount of data transmitted by smart devices, there is an urgent need to unlock smart technologies and sendees with investments on the scalability of computational resources. This objective can be achieved by means of a standardized software platform that can support interoperability and behave as the main vehicle for the rapid implementation of innovative energy sendees. One possibility to enhance computational power on demand is cloud computing, which forms the Internet of Things (IoT). In this work, a customizable open-source IoT platform setup using the FIWARE framework is deployed, which exploits the advantages for a smart energy domain. The term platform comprehends a set of software tools that allow quick integration of various devices. This study presents the implemented platform and analyses its functionality in different use cases on the European level.